(untitled) - Megha p. Nanhe (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The process of hiring employees for human in Investment in organization via electronic resources like Linkedin, naukari.com etc, is considered as E-recruitment. In this process, job applications call online through different platforms, so e-recruitment can complete quickly. Most of the companies follows E-recruitment process to hire employees as well as it helps to select appropriate candidates for an appropriate post. The goal of this paper to analyze the important points influencing the achievement of e-recruitment in selected companies. The conclusion disclose that the companies implement this process to decrease the expenses for hiring candidates and improve the productivity.